Parental Influences on Elite Aesthetic Athletes’ Body Image Dissatisfaction and Disordered Eating - Francisco, Rita (2013)
Although different forms of parental influences on adolescents’ body image and eating disturbances have been studied, this relationship is nearly uninvestigated within the population of aesthetic athletes, a risk group for the development of eating disorders. The present study examined the role of specific family variables on the body image dissatisfaction (BID) and disordered eating (DE) of elite aesthetic athletes (n = 85) and controls (n = 142). Adolescents (M = 14.87 years, SD = 2.22) completed measures of direct influences (concern with thinness and weight teasing by parents), perceived quality of relationship with each parent and the overall family environment, BID and DE. Participants’ parents (223 mothers and 198 fathers) also completed measures of BID and DE. In general, parents of athletes do not present higher levels of BID or DE than do controls’ parents. Interesting differences were found between athletes’ and controls’ BID and DE predictors. Among athletes, direct parental influences are the only significant predictive family variable, which can reinforce the pressure to be thin found within elite-aesthetic contexts. The study’s findings highlight not only the importance of critical parental comments in athletes’ expression of BID and DE, but also of maternal modeling among adolescents in the general population. Such parental behavior may be an appropriate target in different prevention efforts.